El poblamiento prehistorico en la Cuenca de! Mediana (Alt Penedes, Barcelona) - Esteévez, J.; Piqué, R.; Vila, A.; Taulé, M.; Weniger, G.; Bonet, A.; Clemente, I. (Trabalhos de Antropologia e Etnologia, 2020)
.